Histopathological Study of Carcinoma Cervix through Reviewing of Female Genital Tract Cancer Cases of Pathology Archive, Benghazi University from (2002-2011) - Alashger, Abeer M. F.; Amer, Abeer H. A.; Benhasouna, Ahmed A. M. (Scientific Journal of University of Benghazi, 2021)
Female genital tract (FGT) is the most common site for tumors in females. The most common type of (FGT) cancers is cervical, ovarian and endometrial carcinoma. There are other less common tumor's including tumors of the vagina, vulva and fallopian tubes. Cervical cancer is the second most commonly diagnosed cancer worldwide and the fourth leading cause of cancer death in women. To determine the frequency of (FGT) malignancy found at the pathology archive of the Pathology Department at the Faculty of Medicine in the University of Benghazi between the years 2002-2011. Also to define the proportion of cervix cancer cases as compared with other (FGT) that were recorded in the archive. Moreover, to study the histopathological type of cervical cancer, the age groups and at which grades of differentiation are mostly determined. Retrospective histopathological analysis of (FGT) 330 cancer cases diagnosed between (2002-2011). During the reviewing of (FGT) cancer cases of pathology archive all cases of cervical cancer between 2002-2011 were collected and all formalin-fixed paraffin-embedded (FFPE) tissue blocks of the patients with cervical cancer in that period were collected, and processed to stained slides. In an analysis of 330 FGT cancer cases registered in the pathology archive. (52%) were carcinoma of the endometrium and this was the commonest. This was followed by the carcinoma of the cervix (30.9%), ovarian tumors (13%), vaginal tumors (2%), fallopian tumors and vulva tumors (1%). The most common type of carcinoma cervix was squamous cell carcinoma (62%), adenocarcinoma was (31%) and the least common type was adenosquamous carcinoma (7%). The mean age of patients was 54.67 years. Most cases presented at the postmenopausal period (62.5%). Most cases were poorly differentiated (47.1%), followed by moderately differentiated (33.3%) and well-differentiated (17.6%).